Zastosowanie skalowania Rascha do oceny trafności skali pomiarowej - Węziak, Dorota (Assessment of the validity of the scale with the Rasch model, 2006)
The aim of the article is to present the Rasch Model and its application to the assessment of the validity of the scale. The article begins with the presentation of the method pointing out the differences between the Rasch Model and the Rasch Rating Scale Model. Then the techniques for detecting item bias with the Rasch Model are presented. The theoretical part of the article is followed by the application part where items of the scale measuring attitude towards the old are verified in terms of the bias.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1142, s. 34-48